190k views
4 votes
What is a3b4−−−−√ expressed in simplified form?

a2bb√

ab2a√

ab2ab−−√

abab−−√

User Tys
by
5.8k points

1 Answer

4 votes

Answer:


ab^2√(a)

Explanation:

We are asked to express
√(a^3b^4) in simplified form.

Using radical rule
√(mn)=√(m)\cdot √(n), we will get:


√(a^3b^4)=√(a^3)\cdot√(b^4)

Rewrite
a^3 as
a^2\cdot a and
b^4 as
(b^2)^2


√(a^3b^4)=√(a^2\cdot a)\cdot√((b^2)^2)

Using radical rule
√(mn)=√(m)\cdot √(n), we will get:


√(a^3b^4)=√(a^2)\cdot√(a)\cdot√((b^2)^2)

Using radical rule
\sqrt[n]{m^n}=m,we will get:


√(a^3b^4)=a\cdot b^2\cdot√(a)


√(a^3b^4)=ab^2\cdot√(a)

Therefore, the simplified form of the given expression would be
ab^2√(a).

User George Mylonas
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.